2019
DOI: 10.1149/2.0211907jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Water Removal from PEM Fuel Cells Using Acoustic Pressure Waves

Abstract: Liquid water management remains a primary challenge in developing next generation low temperature proton exchange membrane fuel cells. This work demonstrates the use of acoustic pressure waves superimposed on reactant channel air flow as an effective means to enhance liquid water removal from gas diffusion layer surfaces. Experiments were conducted for a range of acoustic vibration frequencies; 20 to 120 Hz with 20 Hz intervals. Water transport was visualized using a CCD camera mounted over a transparent ex-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Schafer et al managed to superimpose an acoustic wave to excite the liquid surface. Using acoustic pressure waves superimposed on the air flow, Mortazavi et al investigated the water removal behavior from GDL surfaces. Transparent channel and a CCD camera were adopted to observe the water transport in their study.…”
Section: Introductionmentioning
confidence: 99%
“…Schafer et al managed to superimpose an acoustic wave to excite the liquid surface. Using acoustic pressure waves superimposed on the air flow, Mortazavi et al investigated the water removal behavior from GDL surfaces. Transparent channel and a CCD camera were adopted to observe the water transport in their study.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers 69,70 have shown that pore‐size distribution affects mass transport more than the total porosity. It was found that increasing the MPL volume in the GDL decreased the fuel cell overall performance loss due to mass transport limitations 10 . GDL with non‐uniformly dispersed porosity has been proposed to improve fuel cell overall performance through supporting water removal and access of gases 71,72 .…”
Section: Basic Pemfc Operationmentioning
confidence: 99%
“…It was found that increasing the MPL volume in the GDL decreased the fuel cell overall performance loss due to mass transport limitations. 10 GDL with nonuniformly dispersed porosity has been proposed to improve fuel cell overall performance through supporting water removal and access of gases. 71,72 Han et al 29 produced an adequate GDL porosity and pore size with the aid of appreciably filling the carbon paper GDL with carbon/PTFE filler to obtain an average pore diameter which was capable of mitigating the flooding of the fuel gas.…”
Section: Gdl Pore Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In PEMFC, the water dispensing method requires gas pressure to force the water droplets to move along the microchannel. Other innovative methods of water removal are, e.g., flexural wave [2], acoustic pressure wave [3], and vibrationalacoustical methods [4]. The average size of the droplet is less than 4 μL [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%